2018
DOI: 10.3389/fnut.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Immunoglobulins on Immune Function, Allergy, and Infection

Abstract: This review aims to provide an in depth overview of the current knowledge of the effects of bovine immunoglobulins on the human immune system. The stability and functional effects of orally ingested bovine immunoglobulins in milk products are described and potential mechanisms of action are discussed. Orally ingested bovine IgG (bovine IgG) can be recovered from feces, ranging from very low levels up to 50% of the ingested IgG that has passed through the gastrointestinal tract. In infants the recovered levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
150
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 185 publications
(216 reference statements)
0
150
0
5
Order By: Relevance
“…Bovine IgG‐enriched preparations protect bacterial infections on several levels via enhancing clearance of pathogens, preventing colonization, and modulating immune functions (Funatogawa et al, ; Ulfman et al, ). Our previous in vitro study using sections made from the cecum wall demonstrated that 5% solution of immunoglobulin‐enriched bovine colostrum significantly blocked the attachment of EHEC O157 to mucous membrane and inhibits the colonization of the bacteria (Funatogawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine IgG‐enriched preparations protect bacterial infections on several levels via enhancing clearance of pathogens, preventing colonization, and modulating immune functions (Funatogawa et al, ; Ulfman et al, ). Our previous in vitro study using sections made from the cecum wall demonstrated that 5% solution of immunoglobulin‐enriched bovine colostrum significantly blocked the attachment of EHEC O157 to mucous membrane and inhibits the colonization of the bacteria (Funatogawa et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The bovine Ig was also found to prevent the replication of human rotaviruses in in vitro tissue culture experiments. This protective effect of bovine Ig has not only been shown for rotavirus in in vivo animal models but also for other pathogens such as enteropathogenic E. coli bacteria (Funatogawa et al, ; Ulfman et al, ) and Helicobacter pylori (Casswall et al, ; Ulfman et al, ). The strongest evidence on protective effects of bovine Ig from non‐immunized cows come from studies in HIV patients with recurrent diarrhoea (Asmuth et al, ; Ulfman et al, ).…”
Section: Biological Effects Of Igmentioning
confidence: 94%
“…This protective effect of bovine Ig has not only been shown for rotavirus in in vivo animal models but also for other pathogens such as enteropathogenic E. coli bacteria (Funatogawa et al, ; Ulfman et al, ) and Helicobacter pylori (Casswall et al, ; Ulfman et al, ). The strongest evidence on protective effects of bovine Ig from non‐immunized cows come from studies in HIV patients with recurrent diarrhoea (Asmuth et al, ; Ulfman et al, ). As HIV patients are severely immunosuppressed as a result of the depletion of CD4 + T cells, they have reduced capacity to resist infections and are highly susceptible to diarrhoea, especially induced by Cryptosporidium, Amoeba and Campylobacter .…”
Section: Biological Effects Of Igmentioning
confidence: 94%
See 2 more Smart Citations